PROFIL ANALISIS BATU SALURAN KEMIH DI LABORATORIUM PATOLOGI KLINIK - G. Ratu; A. Badji (Indonesian Association of Clinical Pathologist and Medical laboratory, 2006)
Urethral stones, or urolithiasis, is a pathologic and condition which is still a frequent problematic issue in the clinic, especially for itsrecurrence. This condition appears mostly in productive-age groups leading to affect their productivity. By stone analysis, the type andthe composition of concretes could be identified, so that the handling of patients could be arranged and its recurrence could be prevented.The study was carried to find out the distribution of urethral stone composition according to age and sex groups. A cross-sectional studyby means of medical records of 199 patients with urethral stone admitted to Dr. Wahidin Sudirohusodo Hospital was carried out duringMay 2002 to May 2004. Analysis was conducted microscopically and macroscopically by colorimetric and titrimetry. Urethral stoneswere found more in men 79.9% (159 of 199) than in women 20.1% (40 of 199). The peak prevalence of age between 31 to 45 yearswere 71.35%, the eldest being 86 years while the youngest was 2 years. The mostly found composition of calcium-oxalate was 87.4%,brushitt was 45.2%, and uric acid was 32.2%. The prevalence of urethral stones was still high, mostly found in 31 to 45 years of agegroup, affecting more men than women, and calcium oxalate showed the highest frequency.